Optical and Electrochemical Properties of Layered Crystals GaSe Intercalated by the Nickel - S.G. Barbutsa; V.B. Boledzyuk; Z.D. Kovalyuk; M.M. Pyrlya; T.M. Feshak (Журнал нано- та електронної фізики)
The presented results of the investigations of the optical and electrochemical properties indicate the possibility of intercalation of layered GaSe crystals with nickel ions. Established that the electrochemical introduction of Ni leads to a monotonic growth in electrode potential of layered semiconductors GaSe when a concentration of intercalants nNi  1018-1020сm – 3. In consequence of intercalation of nickel in GaSe crystal at T  293 K, occurred ncreases in the energy position of the exciton peak Eeks 6 meV (from 2.008 to 2.014 eV) and the half-width of the exciton absorption bands of H by 5.2 meV. At a temperature T  77 K was detected non- monotonous concentration dependence of the excitonic maximum energy location for Еeks NiGaSe compounds. The dependence Еeks(nNi) for these compounds are explained as a result of the introduction of competition between contributions of inter - and intralayer deformations which have the opposite signs of deformation potential.